In Silico Study of Reported Compounds from Togaku Oil Plants from Timor Island as Candidates for Plampesin X Inhibitors of Plasmodium Falciparum - Fallo, Erwince; Bria, Patrisius Maryanto (Universitas Nusa Cendana, 2026)
Malaria is still a major health problem in Indonesia, especially caused by Plasmodium falciparum, so it is necessary to develop new drug candidates to overcome potential antimalarial resistance. This study aims to identify the potential of reported compounds from ToGaku oil-producing plants on Timor Island as candidate inhibitors of the Plasmepsin X protein using an in-silico approach. The structure of Plasmepsin X protein (PDB ID: 7TBC) was obtained from the Protein Data Bank and prepared using YASARA Structure software. Evaluation of structural quality was performed using Ramachandran plot analysis, while active-site prediction was performed using the COACH server. Molecular docking was performed on various candidate compounds using YASARA Structure, with artemisinin as a positive control. Docking results showed that oleanane and dammarane had the highest positive binding energies, (-11,879) kcal/mol and (-8,930) kcal/mol, respectively, which were higher than the positive control, artemisinin (8,428 kcal/mol), indicating stronger binding affinity and a more stable complex. Complex interactions were dominated by hydrophobic residues, including PHE311, ILE316, ILE354, PHE355, ILE358, and PHE360, as well as by polar residues, such as SER246, GLN247, SER269, and THR460, which contributed to complex stabilization. The interaction visualization showed that the selected ligands bind to the protein’s active pocket in a stable orientation. Based on these results, triterpenoid compounds, especially oleanane and dammarane, are potential candidates for Plasmepsin X inhibitors and warrant further experimental testing.